The Effect Of The Economic Recession In The Covid-19 Era And Cash Flows On Financial Performance - Irma Paramita Sofia; Faustine Putri Hotasoit, Anggelly (Jurnal Akuntansi, 2023)
This study aims to explain and understand the effect of the Economic Recession (Decreasing Gross Domestic Product (GDP)) and Cash Flow on Financial Performance, where this research was conducted based on empirical studies on retail trade sub-sector companies listed on the Indonesia Stock Exchange in 2019 – 2021. The population of this research is 28 retail trade sub-sector companies registered on the IDX for the period 2019 to 2021, with a total sample of 69 samples obtained using a purposive sampling method. The data analysis technique is using multiple linear regression analysis with data processing through Eviews12 software. The results of this study reveal that the Economic Recession (Decrease in Gross Domestic Product (GDP)) has an effect on Financial Performance, while Cash Flow has no effect on Financial Performance. Simultaneously, the variables of the Economic Recession (Decrease in Gross Domestic Product (GDP)) and Cash Flows affect Financial Performance. Keywords: Economic Recession, Gross Domestic Product, Cash Flow, Financial Performance